1983
DOI: 10.1042/bj2140153
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in isolated rabbit forelimb muscles. The possible role of metabolites of arachidonic acid in the response to intermittent stretching

Abstract: Protein synthesis was measured in isolated intact rabbit muscles by the incorporation of [3H]phenylalanine added at a high concentration (2.5 mM) to the incubation medium. Intermittent mechanical stretching substantially increased the rate of protein synthesis relative to that in control muscles incubated under a constant tension. Indomethacin and meclofenamic acid, inhibitors of the enzyme cyclo-oxygenase, which converts free arachidonic acid into the prostaglandins, prostacyclins and thromboxanes, decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(38 citation statements)
references
References 27 publications
(26 reference statements)
2
35
0
1
Order By: Relevance
“…Our approach allowed for a detailed time course analysis and demonstrated that addition of nuclei appeared to be most intense 6-9 days after the introduction of overload; this fits previous observations that hypertrophic stimuli initiate satellite cell mitosis before this time period (39)(40)(41). An increase in total protein synthesis (but also in degradation) has already been detected within hours after introducing a hypertrophy stimulus (42)(43)(44)(45), including by hypertrophy models similar to ours (46,47). This has led to speculation that enlargement caused by an increase in synthetic capacity per nucleus precedes addition of nuclei and that nuclei might not be obligatory for hypertrophy.…”
Section: Discussionsupporting
confidence: 81%
“…Our approach allowed for a detailed time course analysis and demonstrated that addition of nuclei appeared to be most intense 6-9 days after the introduction of overload; this fits previous observations that hypertrophic stimuli initiate satellite cell mitosis before this time period (39)(40)(41). An increase in total protein synthesis (but also in degradation) has already been detected within hours after introducing a hypertrophy stimulus (42)(43)(44)(45), including by hypertrophy models similar to ours (46,47). This has led to speculation that enlargement caused by an increase in synthetic capacity per nucleus precedes addition of nuclei and that nuclei might not be obligatory for hypertrophy.…”
Section: Discussionsupporting
confidence: 81%
“…One prostaglandin, PGE2, has been shown to stimulate protein degradation (Rodemann & Goldberg, 1982) and is believed to be involved in some pathological states involving muscle wasting where a large increase in rates of protein degradation has been shown to be inhibited by NSAIDs such as indomethacin and naproxen (Ruff & Secrist, 1984;Tian & Baracos, 1989). PGF2. was shown to stimulate protein synthesis in rat (Rodemann & Goldberg, 1982) and rabbit muscle (Smith et al, 1983) in vitro. The non-steroidal anti-inflammatory drug, indomethacin, which inhibits the action of cyclo-oxygenase and thus reduces the metabolism of arachidonic acid to prostanoids, was shown to inhibit the acute effects of insulin in vivo (Reeds et al, 1985) and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…These observations have implicated cyclo-oxygenase metabolites of arachidonic acid, specifically prostaglandin F2", (PGF2a) (Smith et al, 1983) in the control of protein synthesis. Another NSAID, fenbufen ( a pro-drug, which is metabolized in the liver to 4-biphenyl acetic acid) has also been shown to affect rates of protein synthesis in rat muscle .…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are strong inhibitors of cycloxygenases (COX), and thereby impair the metabolism of arachidonic acid that is necessary for the synthesis of prostaglandins (8). Prostaglandins are able to affect muscle cell proliferation (142), differentiation (96), and fusion (141), and can also modulate muscle fiber growth and the synthesis and degradation of proteins in muscle (104,121). Thus, perturbation of COX activity in either inflammatory cells or in muscle cells would be expected to have broad effects on muscle growth and regeneration following injury.…”
Section: Do Neutrophil-derived or M1 Macrophage-derived Molecules Modmentioning
confidence: 99%